Modeling radiative proton-capture reactions in mid-heavy nuclei - Batziou, E.; Koutsilianou, V.; Stavropoulos, L.; Psaltis, A.; Mertzimekis, T. J. (HNPS Advances in Nuclear Physics, 2019)
A systematic study of (p,γ) reactions was carried out using the reaction codes EMPIRΕ, TALYS and NON-SMOKER (web). The calculated (p,γ) cross sections of seed nuclei 89Y, 107,109Ag, 106,108,110Pd, 112Cd, 121,123Sb, 127I, and 133Cs can be used in a three-fold way: (a) perform an intercomparison of the models in a low-energy regime (b) compare existing experimental data to the theoretical predictions and (c) predict cross sections of reactions planned to be studied experimentally in the near future by our group. The results of the study are presented in a concise way focusing on the experimental conditions.